Malaria, hepatitis B and HIV /AIDS, and their co-infection among Patients Visiting Health Centres in Akure, Nigeria - Afolabi, Olajide Joseph; Aremo, A; H, Oluwabunmi; Itansanmi, I; I, Anuoluwa (Journal of Biomedicine and Translational Research, 2018)
Co-infection is the simultaneous infection of host by multiple pathogenic species, which may co-exist together or not. In this study, the co-infection of malaria, HIV/AIDS and hepatitis B was investigated, using four different locations in Akure, Ondo State. Blood samples were aseptically collected from the left thumbs of 500 respondents using sterile lancets. Thin and thick smear of the blood samples were observed for malaria parasites using X100 magnification of the light microscope. Hepatitis B and HIV/AIDS were tested using diagnostic test kits. The results show that highest prevalence of malaria was observed in Oba-Ile (82.09%) among age group 31-40 years (92.72%).  The lowest prevalence was found in Ala-Ajagbusi (73.17%) among age group 21-30 years (70.03%). Highest prevalence of hepatitis (7.06%) was observed in Orita-Obele while the lowest prevalence was observed in Ala- Ajagbusi (4.88%).  HIV/AIDS infection was found Orita-Obele (1.76%, n=3) and Ala-Ajagbusi (2.44%, n=2). The results further show that all the individuals that tested positive to hepatitis B virus and HIV also tested positive to malaria. Also, 3 of the 5 individuals infected with HIV/AIDS tested positive to hepatitis B virus.  Similarly, malaria, hepatitis B virus and HIV cohabit in 2 individuals; 1 in age group 21-30 years and 1 in age group 31-40 years. Coinfection of malaria with hepatitis and HIV/AIDS suggests that malaria is an opportunistic infection among the hepatitis and AIDS patients. This calls for prompt malaria treatment among the immunocompromised patients. More so, there should be adequate and consistent public health advocacy programs, to enlighten the populace about malaria, hepatitis B and HIV/AIDS in order to completely mitigate the disease spread in the area.